Pragmatic Aspects of Politeness and Translation Techniques in Wicked 2024 Subtitles - Arbain, Arbain; Alsendia, Ibtisam Fairusy; Pane, Widi Syahtia (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Politeness strategies are essential in shaping social interaction and maintaining harmony, particularly in audiovisual translation where linguistic and cultural nuances must be preserved. Specific Background: In the 2024 film Wicked, English dialogues rich in politeness markers are rendered into Indonesian subtitles, facing constraints of space, time, and cultural divergence. Knowledge Gap: While prior studies address politeness strategies or subtitle translation techniques separately, few explore their interplay in Indonesian subtitles for contemporary films. Aims: This study investigates the types of politeness strategies in Wicked’s dialogues and examines the translation techniques applied in their Indonesian subtitles, evaluating their impact on pragmatic meaning. Results: Using Brown and Levinson’s politeness theory and Molina and Albir’s translation taxonomy, findings show positive politeness as the most frequent strategy and literal translation as the most applied technique, though modulation better preserved pragmatic force. Subtitling constraints sometimes altered politeness nuances. Novelty: This research uniquely maps the relationship between politeness strategies and translation techniques in Indonesian subtitles, providing a nuanced understanding of pragmatic preservation in film translation. Implications: The study underscores the need for pragmatic awareness in subtitle translation, advocating for techniques sensitive to both linguistic accuracy and cultural context to enhance cross-cultural communication in audiovisual media. Highlights: Positive politeness dominates Wicked’s dialogues, while modulation better preserves pragmatic force than literal translation. Subtitling constraints can reduce or alter politeness nuances, affecting cross-cultural meaning. Pragmatic awareness is essential for translators to balance linguistic accuracy with cultural sensitivity. Keywords: Politeness Strategy, Translation Technique, Wicked 2024, Subtitle, Pragmatics